Prone Positioning for Successful Gamma Knife Radiosurgical Treatment of Far Anterior Skull Base Lesions: A Technical Note - Clarke, Michelle J.; Foy, Andrew B.; Garces, Yoldana I.; Link, Michael J. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Gamma Knife targeting is geometrically limited by the physical dimensions of the head, helmet, headframe, and the radiation target position. All four aspects need to be considered for accurate treatment planning. Within the available space, delivery of the treatment isodose is based on the target position, which must be brought into the center of the collimator. In cases of anatomically challenging target positions in far eccentric locations of the head, careful treatment planning needs to be performed that does not exceed the limits of the system.Clinical Presentation We describe a case of a challenging far anterior ethmoid sinus hemangiopericytoma in an 80-year-old woman.Technique The tumor was treated successfully by positioning the patient prone on a Model C Gamma unit. The physical restrictions of the Gamma Knife surgical system and the rationale for improved anterior targeting using the prone position are discussed.Conclusion A thoughtful approach to positioning in challenging anterior lesions extends the targeting capabilities of certain Gamma units.
Keywords: radiosurgery; gamma knife; hemangiopericytoma; prone position